The God who justifies a comprehensive study of the doctrine of justification - White, James Robert, 1962- (Bloomington, MN Bethany House, 2001)
Includes bibliographical references and indexes.
Keywords: Justification (Christian theology) -- biblical teaching; Bible. N.T. Epistles -- criticism, interpretation, etc